Pemberian Kotoran Ayam dan Abu Janjang terhadap Pertumbuhan Elaeis guineensis Jacq di Pre Nursery - Wahyu Prabowo; Bayu Pratomo; Julaili Irni; Nur Ariyani Agustina; Aisar Novita (Seminar Nasional Lahan Suboptimal, 2020)
Prabowo W, Pratomo B, Irni J, Agustina N. A, Novita A. 2020. Application of dung and empty fruit bunch to elaeis guineensis jacq growth in pre nursery. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).In an effort to implement zero waste management in oil palm plantations, bunch ash which is a waste product from palm oil mills can be used as fertilizer for oil palm plants. This study aims to determine the growth of oil palm seedlings after being given different doses of dung from chicken and bunch ash fertilizer. This study used an experimental method with a factorial randomized block design (RBD). The first factor is chicken manure which consists of 4 levels, namely: Control (P0), 70 gr (P1), 140 gr (P2), 210 gr (P3) and the second factor is oil palm basket ash fertilizer which consists of 4 levels namely: Control (A0), 13 gr (A1), 26 gr (A2), 39 gr (A3). The data obtained were analyzed using analysis of variance (Analysis of Variance) with a significant 5%. If it has a significant effect, continue with the Duncan's Multiple Range Test (DMRT). Based on the results of the data analysis, it was found that the treatment of chicken manure did not have a significant effect on plant growth (shoot wet weight, shoot dry weight, root wet weight, root dry weight and root length), and the interaction did not significantly affect the growth of oil palm seedlings in pre nursery. Although some of the parameters tested did not show any statistical effect, the physical growth of oil palm seedlings produced seeds that still met the seed growth standards in the pre-nursery.